Digital Payment In Nepal: An Overview And Recommendations (Rupandehi Campus Journal, 2024)
Information technology (IT) has completely changed many facets of our lives; in particular, it has made it simple to make digital payments. The general public began to switch from traditional payment methods to digital ones that offered convenience, safety, and security. Modern payment methods were made possible by the development of information and communication technology. People’s lives were made easier by the proliferation of smartphones and internet access, which also ushered in the age of digitalization. In addition to enhancing trade and commerce, digitalization also made payment transactions simple and quick. The goal of the current study is to understand the various kinds of digital payment transactions that regular people use in their day-to-day lives, as well as the current state of the industry and Nepal’s growth prospects. The primary data used in this study are secondary data. The outcome suggests that the digital revolution has made transactions involving less cash simple.